New insights into the repressor role of PqsE over pqsA - Romo Catalán, Natalia Valentina (2022)
Pseudomonas aeruginosa is an opportunistic pathogen able to thrive in a wide variety of environments. Its highly diverse and adaptable behaviour is an increasing threat in chronic and hospital acquired infections (HAI). The exceptional ecological success of P. aeruginosa can be attributed to its vast metabolic versatility and its sophisticated cell- to- cell communication system quorum sensing (QS). QS network enables P. aeruginosa control the expression of diverse virulence factors such as pyocyanin, elastase, exotoxins, rhamnolipids, and biofilm formation. QS in P. aeruginosa is closely regulated by at least three different but highly interconnected systems namely, the Las, Rhl, and quinolone-based QS system, PQS. The PQS system acts mainly via 2-heptyl-3-hydroxy-4-quinolone, named the Pseudomonas quinolone signal (PQS), which connects the LysR-type transcriptional regulator PqsR to stimulate their own synthesis along with the expression of several virulence factors. The synthesis of PQS is driven by the pqsABCDE operon, phnAB and pqsH, located further in the P. aeruginosa genome. PqsE, encoded by the last gene of the pqs operon, functions as a pathway-specific thioesterase involved in the synthesis of HHQ and PQS, however its role in this pathway can be replaced by the broad-specificity thioesterase TesB, which reveals why pqsE deletion mutants maintains the synthesis of PQS. PqsE also adds independent roles onto the control of bacterial virulence through an unidentified mechanism. Among others, it balances the levels of QS signal molecules and secondary metabolites deriving from the PQS pathway by repressing the pqsA promoter, however, since PqsE does not possess DNA binding domain, its molecular mechanism remains elusive. Previously at the University of Nottingham, two DNA promoter pull down analysis were performed in a PAO1 pqsE Ind strain. In this setup, the overexpression of pqsE at the early and late stage of growth of P. aeruginosa showed a diverse protein profile binding the pqsA promoter, suggesting that they could potentially act as intermediate of the action of this effector in this regulation.